ANALYSIS OF ENGLISH NEEDS IN STUDENTS OF NURSING STUDY PROGRAM STIKES NGUDIA HUSADA MADURA - Dhaniel Prasetyo Irianto; Emi Nurniati (Universitas Pahlawan Tuanku Tambusai, 2022)
This study is at identifying and analyzing the needs of ESP learning material in learning English at diploma nursing students. To find out the correct reference, analysis is urged to be done to obtain information about what the students really need to support their learning process at the present time or in the future career. This study was conducted by using a qualitative approach and descriptive method. The samples were students from Diploma Nursing Study Program of STIKes Ngudia Husada Madura who are currently taking English subject and the sampling technique used was purposive random sampling. Meanwhile, a questionnaire as the instrument for this study was arranged in a closed-ended form. The data analysis was descriptive analysis in the form of number and percentage. The study revealed that the needs of nursing students on English subjects are very diverse and it can be concluded that they need English not only for their current needs as they can communicate in English to support their education in the nursing field, but also for their future professional careers. Therefore, it is recommended that ESP English lectures or other related parties should accommodate the needs of these students. In addition, it is suggested to always conduct needs analysis since the needs of ESP learners are constantly changing. Keywords: ESP, English subject, needs analysis, learners' needs